A micro-sized vaccine based on recombinant Lactiplantibacillus plantarum fights against SARS-CoV-2 infection via intranasal immunization - Letian Li; Jiayi Hao; Yuhang Jiang; Pengfei Hao; Yuwei Gao; Jing Chen; Guoqing Zhang; Ningyi Jin; Maopeng Wang; Chang Li (Elsevier, 2023)
COVID-19 has globally spread to burden the medical system. Even with a massive vaccination, a mucosal vaccine offering more comprehensive and convenient protection is imminent. Here, a micro-sized vaccine based on recombinant Lactiplantibacillus plantarum (rLP) displaying spike or receptor-binding domain (RBD) was characterized as microparticles, and its safety and protective effects against SARS-CoV-2 were evaluated. We found a 66.7% mortality reduction and 100% protection with rLP against SARS-CoV-2 in a mouse model. The histological analysis showed decreased hemorrhage symptoms and increased leukocyte infiltration in the lung. Especially, rLP:RBD significantly decreased pulmonary viral loads. For the first time, our study provides a L. plantarum-vectored vaccine to prevent COVID-19 progress and transmission via intranasal vaccination.